City Narratives as Places of Meaningfulness, Appropriation and Integration - Novak, Sonja; Sioli, Angeliki; Oliveira, Susana; Havik, Klaske (Writingplace, 2022)
This issue is an invitation to look beyond the definitions of meaningfulness, appropriation and integration, and explore the relations between them. We have liberally arranged the articles under the three main themes but, as it can easily become clear, there are overlaps among the themes. In that way, this issue offers not only a geographical journey along different urban narratives, but also an expedition into the network of interrelated terms and spatial practices.